An Old Nubian Curse from the Faras Cathedral - van Gerven Oei, Vincent W.J. (Études et Travaux, 2019)
The present paper analyses an Old Nubian inscription from the Faras Cathedral, containing a curse with a reference to Col 1:13. The publication gives a description of the inscription, a transcription with critical apparatus, and a grammatical and general commentary on the text.